Analisis Pengetahuan Investasi, Return, dan Risiko Terhadap Minat Berinvestasi Online di Aplikasi Bibit - Keisya Tri Amanda; Ahmad Albar Tanjung (Politeknik Ganesha Medan, 2023)
This study will evaluate and assess investment knowledge, as well as returns and risks to an interest in investing online in BIBIT applications. The goal of this research is to measure and analyze investment knowledge. The amount of interest one has in making investments is serving as the dependent variable for this investigation. Because of the more rigorous and planned approach that this research method takes to the collection and analysis of numerical data, it can be classified as a type of quantitative research. For both the collecting and the analysis of data, this study relied on primary sources. Whereas the primary data is made up of information that was acquired through the direct and online distribution of questionnaires using a Google form, the secondary data is made up of information that was gathered through other means. The survey was completed by one hundred individuals, and the researchers collected a total of fifty samples from those individuals. The sample determination technique used a purposive sampling technique. The young people who take part in seed applications are the ones who are targeted and targeted for this activity. According to the data, having knowledge in investing led to an increase in the level of investment interest displayed in BIBIT applications. Increased investing activity is typically encouraged when a higher rate of return is offered. In a similar vein, there is a connection between the risk of an investment and the interest in that investment.